Microwave plasma-induced growth of vertical graphene from fullerene soot - Zhipeng Wang; Yipei Li; Jian Liu; Gui Tian; Gang Liu; Mingxi Wang; Hironori Ogata; Wei Gong; Adavan Kiliyankil Vipin; Gan, Melvin Jet Hong; Josue Ortiz-Medina; Shingo Morimoto; et al. (Elsevier B.V., 2021)
Vertical graphene (VG) films can be fabricated on the surface of nickel foil from fullerene soot (FS) under microwave plasma irradiation (MPI) in a mixture gas of H2 and Ar at 1200 W for 15 min. The resulting FS-derived VG films mostly consist of few-layer graphene sheets with large domain graphene sizes, high graphitization order, and high purity, as characterized by scanning and transmission electron microscopies, Raman spectroscopy, and X-ray photoelectron spectroscopy. Combined the present and previous results, MPI technique is an effective and versatile approach to synthesize vertically oriented graphene sheets from any carbon-containing sources.